Plasmon induced thermoelectric effect in graphene. Issue 1 (December 2018) - Shautsova, Viktoryia; Sidiropoulos, Themistoklis; Xiao, Xiaofei; Güsken, Nicholas; Black, Nicola; Gilbertson, Adam; Giannini, Vincenzo; Maier, Stefan; Cohen, Lesley; Oulton, Rupert
Abstract Graphene has emerged as a promising material for optoelectronics due to its potential for ultrafast and broad-band photodetection. The photoresponse of graphene junctions is characterized by two competing photocurrent generation mechanisms: a conventional photovoltaic effect and a more dominant hot-carrier-assisted photothermoelectric (PTE) effect. The PTE effect is understood to rely on variations in the Seebeck coefficient through the graphene doping profile. A second PTE effect can occur across a homogeneous graphene channel in the presence of an electronic temperature gradient. Here, we study the latter effect facilitated by strongly localised plasmonic heating of graphene carriers in the presence of nanostructured electrical contacts resulting in electronic temperatures of the order of 2000 K. At certain conditions, the plasmon-induced PTE photocurrent contribution can be isolated. In this regime, the device effectively operates as a sensitive electronic thermometer and as such represents an enabling technology for development of hot carrier based plasmonic devices. The photoresponse of graphene-based photodetectors is dominated by photovoltaic and photothermoelectric effects. Here, the authors leverage strongly localised plasmonic heating of graphene carriers to detect a second photothermoelectric effect occurring across a homogeneous channel in the presence of an electronic temperature gradient.